An ancient family of human endogenous retroviruses encodes a functional homolog of the HIV-1 Rev protein - Yang, Jin (The National Academy of Sciences, 1999)
The human endogenous retrovirus K (HERV-K) family of endogenous retroviruses consists of ≈50 proviral copies per haploid human genome. Herein, the HERV-Ks are shown to encode a sequence-specific nuclear RNA export factor, termed K-Rev, that is functionally analogous to the HIV-1 Rev protein. Like HIV-1 Rev, K-Rev binds to both the Crm1 nuclear export factor and to a cis-acting viral RNA target to activate nuclear export of unspliced RNAs. Surprisingly, this HERV-K RNA sequence, which is encoded within the HERV-K long terminal repeat, is also recognized by HIV-1 Rev. These data provide surprising evidence for an evolutionary link between HIV-1 and a group of endogenous retroviruses that first entered the human genome ≈30 million years ago.